JAMS@AX24 Conference Report - Emilie Waggoner; Jaclyn Koshofer (Journal of Anime and Manga Studies)
The JAMS@AX Academic Symposium, an academic conference inside of Anime Expo 2024, brought together scholars, librarians, educators, and enthusiasts from around the world to explore the academic study of anime, manga, and Japanese culture. The Journal of Anime and Manga Studies partnered with Anime Expo to co-host this conference for the second time following last year’s MechaJAMS symposium, continuing to offer this unique opportunity to delve deeper into the world of Japanese pop culture on a scholarly level. This year, the symposium embraced the “Edo Japan” theme and encouraged presenters to discuss how anime presents Japanese history and culture, especially during this period. The symposium offered a diverse array of panels and presentations that delved into various aspects of anime and manga studies, from historical reinterpretations and cultural critiques to the impact of music and the integration of traditional art forms. This report provides an overview of the key discussions and insights shared during the symposium, highlighting the scholarly contributions and the vibrant exchange of ideas that marked the event.